Pengaruh Penerapan Green Accounting Terhadap Sustainable Development Dengan Ukuran Perusahaan Sebagai Variabel Intervening - Gialuna Cheshaa Trevanti; Anik Yuliati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to test and analyze the effect of implementing green accounting as measured through environmental performance assessment indicators on sustainable development as measured through the GRI G4 index with company size as the intervening variable. This study uses a quantitative approach. The research sample consisted of 8 companies from 93 population of basic materials sector companies on the Indonesia Stock Exchange (IDX) for the 2017-2021 period which were determined using a purposive sampling technique. Data analysis techniques were performed using the Partial Least Square (PLS) method with the help of SmartPLS 4.0 software. This research data is secondary data in the form of annual reports and sustainability reports obtained from the official website of each company. The results of the study found that green accounting has a positive and significant influence on sustainable development and company size. In addition, with regard to sustainable development it was found that company size did not have a significant effect, either as an independent variable or an intervening variable. Keywords: Green Accounting, Company Size, Sustainable Development